Mechanistic pathways of fibromyalgia induced by intermittent cold stress in mice is sex-dependently - Carolina C. Martins; Angélica S. Reis; Ketlyn P. da Motta; Cristiane Luchese; Ethel A. Wilhelm (Brain Research Bulletin, 2022)
Fibromyalgia results from a complex interplay of biochemical and neurobiological elements mediated sensitization of nociceptive pathways. Despite the symptoms of fibromyalgia negatively affect the quality of life of patients, the pathophysiology of this disease remains inconclusive, which difficult the development of an appropriate treatment. The present study investigated the involvement of the serotonergic receptors, the N-methyl-D-aspartate (NMDA)/ nitric oxide (NO)/ cyclic guanosine monophosphate (cGMP) pathway and the oxidative stress in an animal model of fibromyalgia induced by intermittent cold stress (ICS), considering the specificities of male and female Swiss mice. The ICS exposure increased mechanical and thermal sensitivities, and decreased muscle strength in mice of both sexes. Female mice exhibited a longer-lasting mechanical sensitivity than male mice exposed to ICS along with an enhancement of the Na+, K+-ATPase activity in the spinal cord and cerebral cortex. Conversely, an inhibition in the Na+, K+-ATPase and glutathione peroxidase activities accompanied by an increase in the reactive species levels in the cerebral cortex of male mice were observed. The treatment with different serotonergic antagonists (pindolol, ketanserin and ondasetron) reversed the mechanical sensitivity in mice of both sexes, after the ICS exposure. The administration of MK-801, L-arginine and methylene blue also blocked the mechanical sensitivity in female mice exposed to ICS. Except L-arginine, MK-801 and methylene blue also attenuated this nociceptive signal in male mice, after ICS exposure. In conclusion, the modulation of serotonergic receptors, the NMDA/NO/cGMP pathway, and the oxidative stress seems contribute to nociceptive behaviors induced by ICS exposure sex-dependent.